Enduring Pasts and Denied Presence: Mi’kmaw Challenges to Continued Marginalization in Western Newfoundland - Robinson, Angela (Anthropologica, 2014)
Prior to the 1970s much of the anthropological research conducted in Newfoundland and Labrador focused on either Inuit, Innu or Beothuk populations, a fact that can be attributed to the failure of provincial and federal governments to formally recognize the Ktqamkukeweq (Newfoundland) Mi’kmaq. This study documents the ways in which the Newfoundland Mi’kmaq challenge the institutions and practices that serve to assimilate and suppress them. As an anthropology of decolonization, this research supports Aboriginal peoples in resisting colonial projects of assimilation and the dispossession of lands and resources by providing a counter-discourse to settler notions of what constitutes Aboriginal rights and claims to Aboriginality.